Análise da influência do espaçamento interlamelar da perlita nas propriedades mecânicas do aço AISI 1080 - Frota, Ranna Alves (2023)
In eutectoid steel in accordance with 1080 standard, thermal processes allow the formation of different microstructures, which providence this type of steel with diferrent applications. In this context, heat treament techniques emerge that make it possible to obtain the pearlitic structure, which is characterized by the coexistence of two phases composed of alternating layers of cementite and ferrite. The spacing between these layers of perlite plays an important role in the property changes of the steel exhibiting this microstructure. The objective of this study is to evaluate how the interlayer spacing of perlite of pearlite affects the mechanical characteristics of 1080 steel when subjected to different heat treatments conditions. The analysis of the microscopic structure of the samples was carried out with the help of a scanning electron microscope. Hardness results were obtained using Vickers microhardness (HV) and Rockwell C hardness (HRC) tests. According to the results, it can be stated that the transformation temperature exerts a considerable influence on the interlayers spacing of the perlite, which, when reduced, results in an increase in microhardness.